Dzyaloshinskii–Moriya interaction manipulation in multiferroic Janus monolayers - Xuanyi Li; Zhiwen Wang; Zefeng Chen; Zhichao Yu; Changsong Xu (npj Computational Materials)
Abstract The discovery of two-dimensional (2D) multiferroic materials leads to significant breakthroughs in condensed matter physics. However, the role of Dzyaloshinskii–Moriya interaction (DMI) in determining the magnetic and ferroelectric orderings of 2D multiferroics remains underexplored. In this study, we employ first-principles calculation methods to reveal the multiferroic nature of Janus NiXY monolayers (X, Y = I, Br, Cl). Our analyses demonstrate that, (i) Janus NiXY magnets exhibit a cycloid helical spin ground state propagating along the 〈110〉 direction, dominantly driven by intrinsic DMI; and (ii) macroscopic ferroelectric polarizations are intertwined with spin spiral orders, indicating their type-II multiferroicity. Notably, the inclination of the spin rotation plane directly correlates with the DMI strength, which suggests adjustable electric polarization when spin-spin interactions are modulated by external electrostatic fields. Therefore, our work not only indicates the DMI manipulation for tailoring magnetic and ferroelectric ground states but also highlights the intrinsic strong magnetoelectric coupling effects in multiferroic Janus materials.